Reimagining Accessibility for Deaf Youth Through Multimedia Education Across South and South Asia - Kayastha, Sangeet; Kumar, Nishant; Maharjan, Safalta; Shrestha, Anju (Awnu) (Nepalese Journal of Management Science and Research, 2026)
Deaf and Hard-of-Hearing (DHH) youth often face significant barriers in accessing Sexual and Reproductive Health and Rights (SRHR) information because most education and health communication systems are not designed with accessibility in mind. Limited availability of sign language resources further restricts their participation in health education. This study explored a peer-led digital media initiative implemented in Nepal, Bhutan, Laos, and Pakistan. Forty-eight deaf youth participated in producing sign language–based podcasts and multimedia content over one year. Digital platforms such as YouTube and podcast channels were used to share the content, supported by subtitles and offline distribution to improve accessibility. Audience feedback and digital engagement were used to understand the initiative’s reach and impact. The project produced multiple SRHR-focused episodes and created a platform for deaf youth to share lived experiences and communicate health information in sign language. Peer-led storytelling strengthened participants’ confidence and encouraged inclusive community dialogue on SRHR topics. Accessible digital media and youth-led storytelling can help bridge communication gaps in SRHR education and support more inclusive health communication for deaf communities.